Fundamentals of geotechnical engineering - Das, Braja M.; Sivakugan, N. (Cengage Learning, 2017)
This valuable, cohesive book focuses on the fundamental concepts of both soil mechanics and foundation engineering without the distraction of excessive details or cumbersome alternatives. A wealth of worked-out examples and useful supporting figures help your students master key concepts and gain essential problem-solving skills.